Cochlear implants and drug delivery: In vitro evaluation of dexamethasone release. Issue 2 (30th August 2013) - Astolfi, Laura; Guaran, Valeria; Marchetti, Nicola; Olivetto, Elena; Simoni, Edi; Cavazzini, Alberto; Jolly, Claude; Martini, Alessandro
Abstract Anti‐inflammatory drugs can minimize the trauma and inflammation in the inner ear caused by cochlear implantation surgery. For this reason, much effort has recently been devoted to finding the best way to administer these anti‐inflammatory drugs for a prolonged time and in a personalized dosage. One solution is constructing an electrode with a dispenser filled with anti‐inflammatory drugs with a dosage adapted to suit each new cochlear implant user. The purpose of this study was to measure in vitro, by high‐performance liquid chromatography–mass spectrometry assay, the amount of dexamethasone released in 78 days in a physiological solution by a filled dispenser. The drug release continued for more than 2 months in three different phases: (1) during the first 1–5 days, (2) within about 2 weeks, and (3) from about 3 weeks until the end of experiment. This release trend is in accordance with the 3 main phases of damage caused by the cochlear implantation: (1) insertion trauma within the first 2 days, (2) inflammation within 2 weeks, and finally (3) an intracochlear chronic fibrosis reaction. Future animal model studies should consider using this dispenser in order to establish its effectiveness in preventing damage caused by cochlear implantation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 267–273, 2014.